Online anti-immigrant discourse in Germany: ethnographically backed analysis of user comments - Nann, Leah; Udupa, Sahana; Wisiorek, Axel (Frontiers in Communication, 2024)
This article analyzes discourse-and language-specific features of online anti-immigrant extreme speech in Germany based on a context rich dataset collected through a collaborative coding process involving fact-checkers, ethnographers and natural language processing (NLP) researchers. The analysis reveals that direct forms of racism intertwine with argumentative forms of antagonism and playful word games within anti-immigrant discourses, in ways that center a narrative of victimhood and perceived physical and cultural threats from migrants. Offering a bottom-up annotation scheme to capture the nuances of such discourses, we also develop a typology of lexical innovations. By combining critical discourse analysis with a linguistic perspective, we show how the specific conditions in Germany including strict legal regulations of speech, have shaped the emergence of a non-standard language variety in and through anti-immigrant discourse, which also allows this discourse community to maintain group identity.